Effectiveness of gliocladium virens in controlling Fusarium oxysporum F. sp. capsici disease on chilli plant - Afriani, Astri; Heviyanti, Maria; Harahap, Fitra syawal (Jurnal Online Pertanian Tropik, 2019)
Wilt disease which is caused by Fusarium oxysporum f. sp. capsici is one of the important diseases in chili plants that can reduce growth, fruits yield, quality, and chili production. This fungus comes inside the vascular bundle through the root tissue and quickly colonizes in xylem vessels and causing typical wilt symptoms on plants. In line with the development of organic farming systems, biological control by using biological agents is the prospective method in controlling diseases on the plant. Gliocladium virens are one of the biological agents that obstruct the spreading of disease. The aim of this study was to determine the effectiveness of Gliocladium virens in controlling Fusarium oxysporum f. Sp. Capsici on chili plant. This research used randomized block design with two factors: 1 The Time application of Gliocladium virens (W) factor; 2. Dosages of Gliocladium virens (D). The results show that on the treatment time of application of Gliocladium virens W1 of 0.06, W2 of 0.05, W3 of 0.09 and W4 of 0.08 were not significantly different. The treatment given Gliocladium virens disease intensity at week 3 was lower that is equal to 0.125% compared to without treatment of G. virens (D0) the intensity of the disease at week 3 was higher at 1%.